2010
DOI: 10.1242/jcs.069468
|View full text |Cite
|
Sign up to set email alerts
|

The nonsense-mediated decay pathway maintains synapse architecture and synaptic vesicle cycle efficacy

Abstract: SummaryA systematic Drosophila forward genetic screen for photoreceptor synaptic transmission mutants identified no-on-and-no-off transient C (nonC) based on loss of retinal synaptic responses to light stimulation. The cloned gene encodes phosphatidylinositol-3-kinase-like kinase (PIKK) Smg1, a regulatory kinase of the nonsense-mediated decay (NMD) pathway. The Smg proteins act in an mRNA quality control surveillance mechanism to selectively degrade transcripts containing premature stop codons, thereby prevent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 73 publications
1
36
0
2
Order By: Relevance
“…For example, a similar perturbation of visual function has previously been reported upon Jak-Stat activation in the retina following exogenous CNTF treatment [67]. Indeed other kinases are known to regulate visual function; rhodopsin kinase regulates phototransduction, phosphatidylinositol-3-kinase-like kinase (PIKK), cAMP-dependent protein kinase, and the tyrosine kinase insulin receptor regulate photoreceptor synaptic transmission and cAMP-dependent protein, PKC, CaM Kinase, MAP kinase and src family kinases modulate synaptic exocytosis [68][70]. Targets of Pim1 kinase include transcription regulators and proteins involving in cell cycle progression and apoptosis [71].…”
Section: Discussionsupporting
confidence: 66%
“…For example, a similar perturbation of visual function has previously been reported upon Jak-Stat activation in the retina following exogenous CNTF treatment [67]. Indeed other kinases are known to regulate visual function; rhodopsin kinase regulates phototransduction, phosphatidylinositol-3-kinase-like kinase (PIKK), cAMP-dependent protein kinase, and the tyrosine kinase insulin receptor regulate photoreceptor synaptic transmission and cAMP-dependent protein, PKC, CaM Kinase, MAP kinase and src family kinases modulate synaptic exocytosis [68][70]. Targets of Pim1 kinase include transcription regulators and proteins involving in cell cycle progression and apoptosis [71].…”
Section: Discussionsupporting
confidence: 66%
“…Drosophila NMJ synaptic ultrastructure is particularly wellcharacterized, with functionally and spatially defined synaptic vesicle pools organized around presynaptic active zones (containing an electron-dense T-bar) and the muscle subsynaptic reticulum (SSR) molded into elaborate membrane folds (Dani et al, 2014;Long et al, 2010). We therefore next examined Mmp roles in NMJ ultrastructural development using transmission electron microscopy (TEM), with the prediction that mmp2 mutants would show presynaptic defects aligning with the previously observed functional phenotypes (Fig.…”
Section: Mmp1 and Mmp2 Both Regulate Differentiation Of Synapse Functionmentioning
confidence: 75%
“…41 In Drosophila melanogaster, smg1 mutants exhibit significant impairment of the neuromuscular junction synapse structure, and mutation of smg1, upf2 or smg6 greatly reduce neurotransmission and synaptic-vesicle cycling. 42 More recently, we demonstrated that the miR-128 regulates NMD by acting directly on Upf1 and Mnl51 , ensuring proper differentiation of the neural stem cells in mouse and that such action elevated the expression level of many NMD target genes with known neuronal functions, such as Syne1, Robo2, Nrcam and so on. 43 In man, mutations in UPF3B cause ID, along with a spectrum of other neurological defects, which includes autism, attention-deficit hyperactivity disorder and schizophrenia.…”
Section: Discussionmentioning
confidence: 97%